Sustainability Performance of Voided Concrete Slab Using Waste Plastic Bottles - Donald Kwabena Dadzie; A. K. Kaliluthin (Civil Engineering Journal, 2022)
The present study is aimed at investigating the cost assessment of incorporating waste plastic bottles in the manufacture of voided concrete slabs; assessing the depth ratio vis-à-vis the cost reduction of incorporating waste plastic bottles in the manufacture of voided concrete slabs; assessing the energy consumption and CO2 emission obtained by incorporating waste plastic bottles in the manufacture of voided concrete slabs; and evaluating the impact of the depth ratio on embodied energy consumption and CO2 emission. The study was conducted on five types of slab specimens made: (1) conventional solid slab specimens; (2) slab specimens incorporated with 5% air-filled plastic bottles; and (3) slab specimens incorporated with 10% air-filled plastic bottles. Slab specimens of size 1000×1000×150 mm thick incorporated with 0, 5, and 10% waste plastic bottles were considered for the analysis of sustainability with respect to cost, energy, and CO2 savings. As part of the findings, it was revealed that the incorporation of waste plastic bottles into concrete slabs results in a reduction in the cost and volume of concrete. Again, using recycled plastic bottles in the slabs saved money, but for each percentage of bottles used, additional materials (plastic bottles, chicken wire, etc.) and labour were needed, which added to the cost. It was also revealed that embodied energy and CO2 emissions decrease as the percentage of plastic bottles in the slab increases. The study has confirmed that the void slab made with plastic bottles is more sustainable than the traditional solid slab system when it comes to cost, energy use, and CO2emissions. Doi: 10.28991/CEJ-2022-08-11-09 Full Text: PDF